2021
DOI: 10.3390/en14020498
|View full text |Cite
|
Sign up to set email alerts
|

Horizontally Assembled Trapezoidal Piezoelectric Cantilevers Driven by Magnetic Coupling for Rotational Energy Harvester Applications

Abstract: Horizontally assembled trapezoidal piezoelectric cantilevers driven by magnetic coupling were fabricated for rotational energy harvester applications. A dodecagonal rigid frame with an attached array of six trapezoidal cantilevers served as a stator for electrical power generation. A rotor disk with six permanent magnets (PMs) interacted magnetically with the counterpart cantilever’s tip-mass PMs of the stator by rotational motion. Each trapezoidal piezoelectric cantilever beam was designed to operate in a tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Akbari et al proposed the piezomagnetic cantilever beam energy harvester connected to the Savonius vertical axis wind turbine that produced the maximum power of 0.482 mW [28]. In our lab, we have also conducted research on smallscale wind turbines and piezoelectric-wind-power generators with magneto-piezo-elastic structures [29,30]. Recently, a study reported a maximum output of 2.6 W by attaching a piezoelectric cantilever to the bottom of a turbine and generating electricity by using the load generated during the rotation [31].…”
Section: Introductionmentioning
confidence: 94%
“…Akbari et al proposed the piezomagnetic cantilever beam energy harvester connected to the Savonius vertical axis wind turbine that produced the maximum power of 0.482 mW [28]. In our lab, we have also conducted research on smallscale wind turbines and piezoelectric-wind-power generators with magneto-piezo-elastic structures [29,30]. Recently, a study reported a maximum output of 2.6 W by attaching a piezoelectric cantilever to the bottom of a turbine and generating electricity by using the load generated during the rotation [31].…”
Section: Introductionmentioning
confidence: 94%
“…When the excitation magnitude reaches a certain level, nonlinear energy harvesters can effectively extend the response bandwidth of the system and enhance the energy harvesting capability. In the research of nonlinear energy harvesting, magnetic coupling harvesters have received a lot of attention owing to the low manufacturing cost and simple design [9][10][11][12][13]. The most common structure consists of a fixed magnet and a piezoelectric cantilever beam with a tip magnet [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, magnetically coupled energy harvesters have been widely explored to develop nonlinear system (Fu and Yeatman, 2019; Na et al, 2021; Ramezanpour et al, 2016; Xie et al, 2018). The nonlinear magnetic force could effectively overcome the narrow bandwidth issue of the linear energy harvester system.…”
Section: Introductionmentioning
confidence: 99%